The Effect of Life Kinetic Exercise on Performance in Bocce Athletes - Yunus Gür; Sekuş Taşkin; Erdal Sinan Özaktaş; Cengiz Taşkin (Journal of Educational Issues, 2024)
The aim of this study is to examine how life kinetic exercises affect body and mind coordination and shooting performance of bocce athletes in the field of physical education and sports. A total of 40 volunteer men between the ages of 10-12, residing in the city center of Kilis and interested in bocce, participated in this study. Life kinetic exercise was applied to the experimental group for 8 weeks along with bocce training. Only bocce training was applied to the control group. The data were analyzed in the SPSS 26.0 package program. Normality analysis of the data was done with the Shapiro-Wilk test. Paired in the in-group comparison of normally distributed data Sample T-Test was used. At the end of the study, statistically positive significance was determined in the comparison of the pre-test and post-test values of the experimental group. No significant difference was found in the comparison of the pretest and posttest values of the control group. As a result, it can be said that life exercises to be applied in bocce sports, where attention and focus are important, will have positive effects on individuals’ sportive performance.